Feasibility of the echocardiographic subcostal view in newborn foals: two‐dimensional and Doppler aortic findings. (6th April 2018) - Freccero, F.; Cordella, A.; Dondi, F.; Castagnetti, C.; Niinistö, K.; Cipone, M.
Summary: Background: In dogs, due to better alignment with the aortic outflow, the subcostal (SC) transducer site provides greater Doppler‐derived velocities than those obtained from the left parasternal view. The feasibility of this imaging approach has never been described in equine echocardiography. Objectives: The objective of this study was to evaluate the feasibility of the SC view in newborn foals and compare aortic two‐dimensional and Doppler‐derived velocity measurements with those of standard parasternal long‐axis (LAX) views. Study design: A prospective observational study. Methods: Twenty‐three newborn healthy Standardbred and Warmblood foals, aged from 7 h to 6 days, underwent transthoracic two‐dimensional (2DE), M‐mode and Doppler echocardiography that was performed in lateral recumbency. Right and left parasternal long‐axis (R‐LAX, L‐LAX) and SC views were obtained to perform 2DE and Doppler assessments of the aortic valve (AoV). Aortic diameter at the sinus of Valsalva (AoS D) was measured from R‐LAX and SC images. Aortic maximal velocity (AoV Velmax ), velocity time integral (AoV VTI) and pressure gradient (AoV PG) were obtained by pulsed wave Doppler spectra from SC and L‐LAX views. Results: The SC view was feasible in all foals. No significant difference was found in AoS D between different views (P = 0.06), and no significant correlation was detected for bodyweight (BW). AoV Velmax, VTI and PG obtained from the SC view were greater than from the L‐LAX view (P<0.0001, P = 0.0001 and P<0.0001 respectively), especially in foals with lower BW. Main limitations: The order of the transducer site was not randomised among foals, and the observer was not blinded during offline measurement. Conclusions: The SC view can be easily obtained in recumbent newborn foals and provides optimal alignment with aortic outflow, leading to more reliable Doppler flow velocity than the conventional L‐LAX view. Further investigations of the potential use of this view in Doppler estimation of aortic outflow and cardiac assessment of sick foals are recommended.